A Comparative Experimental Analysis of PMSM between Deadbeat Prediction Current Control and Field-oriented Control. (February 2019) - Yunfei, Luo; Chengning, Zhang
Abstract: Traditional field-oriented control (FOC) exists two disadvantages: 1) the PI parameters are difficult to set, 2) the current dynamic response is slow. Compared with FOC, deadbeat predictive current control (DPCC) will result in better dynamic performance and debugging. This paper intends to compare the advantages and disadvantages of DPCC against FOC with simulation and experiment. Two approaches are newly used in the simulation to compare the current-tracking performance, and then the algorithms of DPCC and FOC are experimentally verified based on a 2.6kW permanent magnet synchronous motor (PMSM) control platform. The simulation and experiment results demonstrate that DPCC is suitable for occasions where the PMSM of electric vehicles (EVs) require high dynamic performance, while FOC is more suitable for occasions with high steady-state accuracy.